Impact of Intellectual Capital Disclosure on Corporate Reputation of Bank Pembangunan Daerah Banten: From the Perspective of Acquisition Theory - Fransiska, Vivi Natalia (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2019)
The purpose of this research is to know the Impact of ICD on corporate reputation of Bank Banten from the perspective of acquisition theory. The data is from in Bank Banten’s eight years annual reports (2010 – 2017) annual report. This data analyzed in qualitative manner by employing content analysis method and coded using the IC framework created by Guthrie et al. (2004). The results showed that external capital elements in Bank Banten from holds the biggest word counted in coding process. The most revealed external capital component is the company names. Company names at Bank Banten has impact on Bank Banten’s reputation. Based on the Acquisition perspective, the results of these studies indicate that Bank Banten tend to have a better corporate culture after there is a acquisition process and followed by launch new corporate identity and business strategy.Keywords: ICD, company names, corporate reputation, acquisition theory REFERENCESAbeysekera, I. (2008). Intellectual Capital Disclosure Trends: Singapore and Sri Lanka. Journal of Intellectual Capital.Albrecht, W. S., Stice, E. K., Stice, J. D., & Swain, M. R. (2008). Accounting Concepts and Applications (10 ed.). Mason, USA: Thomson.Arikunto, S. (1998). Prosedur Penelitian Suatu Pendekatan Praktek. Jakarta: Rineka Cipta.Board, F. A. (2001). Business and Financial Reporting: Challenges from the New Economy. Norwalk, CT: Financial Accounting Standards Board.Brännström, D., & Giuliani, M. (2009). Intellectual Capital and IFRS3: A New Disclosure Opportunity. Electronic Journal of Knowledge Management Volume 7 Issue 1, 21-30.Chatzkel, B. M. (2004). Intellectual capital at the crossroads: managing, measuring, and reporting of IC. Journal of Intellectual Capital.Chun, R. (2005). Corporate reputation: Meaning and Measurement. International Journal of Management Reviews.Durrani, E. N. (2017). Market reactions to corporate name changes: evidence from the Toronto Stock Exchange. International Journal of Managerial Finance.Faff, T. J. (2004). What’s in a Name? Evidence on Corporate Name Changes from the Australian Capital Market. Pacific Accounting Review.Freeman, R. E. (1984). Strategic Management: A Stakeholder Approach.García-Meca, E., Parra, I., Larrán, M., & Martínez, I. (2005). The Explanatory Factors of Intellectual Capital Disclosure to Financial Analysts. European Accounting Review.Günther, F. S. (2015). The Relationship between Recognised Intangible Assets and Voluntary Intellectual Capital Disclosure. Journal of Applied Accounting Research.Guthrie, J., & Abeysekera, I. (2006). Content Analysis of social, environmental reporting: What is new? Human Resource nd Costing & Accounting, 114-126. Retrieved from http://www.cpavision.org/vision/wpaper05b.cfm.Guthrie, J., & Petty, R. (2000). Intellectual Capital: Australian Annual Reporting Practices. Journal of Intellectual Capital, 1 (3), 241-251.Guthrie, J., Petty, R., & Yongvanich, K. (2004). Using Content Analysis as a Research Method to Inquire into Intellectual Capital Reporting. Journal of Intellectual Capital Vol. 5 No. 2, 282-293.Ikatan Akuntan Indonesia. (2009). Standar Akuntansi Keuangan. Jakarta: Ikatan Akuntan Indonesia.Ikatan Akuntan Indonesia. (2010). Standar Akuntansi Keuangan. Jakarta: Ikatan Akuntan Indonesia.International Financial Reporting Standard (IFRS) 3 Krippendorff, K. (2004). Content Analysis: An Introduction to Its Methodology. USA: Sage Publication, Inc.Kurniawan, W. W., & Haryanto. (2014). Pengaruh Pengungkapan Intellectual Capital dalam Prospektus terhadap Underpricing Saham (Studi Pada Perusahaan yang Melakukan Initial Public Offering di Bei Periode 2007-2012). Journal of Accounting.Li, J. R., & Haniffa, R. (2008). Intellectual Capital Disclosure and Corporate Governance Structure in UK Firms. Accounting and Business Research, Vol. 38, No. 2, 137-159.Lisa, O. (2012). Asimetri Informasi dan Manajemen Laba: Suatu Tinjauan dalam Hubungan Keagenan. Jurnal Penelitian Ilmu Ekonomi.Marr, B., & Schiuma, G. (2001). Measuring and Managing Intellectual Capital and Knowledge Assets in New Organization. Handbook of Performance.Mase, B. (2009). The Impact of Name Changes on Company Value. Managerial Finance.Merrill, H. J. (2017). Consequences of Information Asymmetry on Corporate Risk Management. Applied Economics Theses.Mohamad, B. B., Rahman, N. A., & Bakar, H. A. (2007). Relationship between Corporate Identity and Corporate Reputation: A Case ofa Malaysian Higher Education Sector. Jurnal Manajemen Pemasaran, Vol. 2, No. 2, 81-89.Moin, A. (2004). Merger, Akuisisi dan Divestasi. Edisi Kedua. Jakarta: Ekonisia.Moleong, L. J. (2007). Metodologi Penelitian Kualitatif. Bandung: Remaja Rosdakarya.Neuendorf, K. A. (2002). The Content Analysis Guidebook. USA: Sage Publication.OECD. (2006). Intellectual Assets and Value Creation: Implication for Corporate Reporting. France: OECD.Project, M. (2002). Guidelines for Managing and Reporting on Intangibles (Intellectual Capital Report). Madrid: European Commission.PSAK No 23 revised 2014.Puspito, H. (2018, February 14). Wartaekonomi. Retrieved from Corporate Reputation, Seberapa Pentingkah?: https://www.wartaekonomi.co.id/read170815/corporate-reputation-seberapa-pentingkah.htmlSastrodiharjo, I. (2014). Efisiensi Modal Intelektual dan Dampaknya terhadap Kinerja Perusahaan. Jurnal Akuntabilitas Vol. VII No. 3.Sawarjuwono, T., & Kadir, A. P. (2003). Intellectual Capital: Perlakuan, Pengukuran dan Pelaporan (Sebuah Library Research). Jurnal Akuntansi & Keuangan Vol. 5, No. 1.Shella, & Wedari, L. K. (2016). Intellectual capital dan intellectual Capital Disclosure terhadap Market Performance pada Perusahaan Publik Indeks LQ-45. Jurnal Akuntansi & Auditing IndonesiaShella1, Linda Kusumaning Wedari2.Sihotang, P., & Winata, A. (2008). The Intellectual Capital Disclosures of Technology-Driven Companies: Evidence from Indonesia. International Journal of Learning and Intellectual Capital, 5 (1), 63-82.Sofian, M. T. (2007). Intellectual capital, management accounting practices and corporate performance: Perceptions of managers. Accounting, Auditing & Accountability Journal.Sugiyono. (2010). Memahami Penelitian Kualitatif. Bandung: Alfabeta.Ulum, I. (2011). Analisis Praktik Pengungkapan Informasi Intellectual Capital dalam Laporan Tahunan Perusahaan Telekomunikasi di Indonesia. Jurnal Reviu Akuntansi dan Keuangan.Utomo, A. I. (2015). Faktor-Faktor yang Mempengaruhi Pengungkapan Modal Intelektual dan Dampaknya terhadap Nilai Perusahaan. Doctoral dissertation, Fakultas Ekonomika dan Bisnis.Widyaningrum, H. A., Sudahak, & Topowijono. (2012). Analisis Tingkat Kesehatan Bank dengan Menggunakan Metode Risk Based Bank Rating (RBBR). Jurnal Administrasi Bisnis, 3-4.Woodcock, R. H. (2011). Firm Characteristics and Intellectual Capital Disclosure by Australian Companies. Journal of Human Resource Costing & Accounting.www.bankbanten.co.idweb.idx.id (old version website of idx.co.id, was accessed in early 2019)www.emeraldinsight.comwww.researchgate.net